Impact of Nitrogen Rate on Maize Yield and Nitrogen Use Efficiencies in Northeast China. (1st January 2015) - Qiu, S. J.; He, P.; Zhao, S. C.; Li, W. J.; Xie, J. G.; Hou, Y. P; Grant, C. A.; Zhou, W.; Jin, J. Y.
Abstract : Optimizing N fertilization is important to improve both maize ( Zea mays L.) yield and nitrogen use efficiencies (NUEs). A 3‐yr maize field experiment (2008–2010) was conducted to evaluate the response of grain yield, aboveground biomass, plant N concentration, N uptake, and NUEs to fertilizer N rates from 0 to 280 kg N ha −1 at three different rain‐fed Haplic Phaeozem soils (FAO classification) in Northeast China. When N application rate increased from 70 to 280 kg N ha −1 across all site‐years, N recovery efficiency, N agronomic efficiency, N internal efficiency and N partial factor productivity decreased from 76.5 to 9.0%, 25.3 to 0.1 kg kg −1, 70.7 to 40.8 kg kg −1, and 145.6 to 22.8 kg kg −1, respectively. Differences observed among the years and experimental sites were primarily caused by variability in rainfall and soil characteristics. The maximal grain yield of 11.0 Mg ha −1 was achieved at an N rate of 210 kg N ha −1 with normal rainfall. Nitrogen application beyond the optimal N rate did not consistently increase grain yield, and caused a decrease in NUEs. The range of optimal N rate for maize grain yield fell between 140 and 210 kg N ha −1 at the three sites from 2008 to 2010 in Northeast China based on the best fitted models (quadratic, linear plus plateau, and quadratic plus plateau). The results provide guidelines for selecting N application rates to optimize both maize yield and NUEs in Northeast China.